Van hoog naar laag: Een alternatief model voor veenontginningen? (Bulletin KNOB, 2024)
In this article the authors draw on three case studies in testing the merits of an alternative peatland reclamation model – namely, from high to low – put forward by several authors in recent years. According to this new model, the drainage of the peatlands started from peat mounds built on top of the dried out peatland, rather than by digging ditches from natural waterways (low) to the centre of the peatland (high). Archaeological and other data for all three case studies – IJsselmonde, Roderwolde and Zeevang – have been analysed as systematically as possible. Roderwolde qualifies as a kind of comparative study. It, too, was considered indicative of an alternative reclamation model but, thanks to extensive archaeological research, we have a fairly detailed picture of this reclamation. In short, it proceeded in accordance with the established model and the peat mounds are a secondary phenomenon. Based on an analysis of the data for IJsselmonde and Zeevang, we conclude that there is as yet no evidence to support the existence of an alternative model. In fact, although the data are incomplete, the drainage methods appear to be consistent with the established model. As in Roderwolde, the peat mounds are a secondary phenomenon: they were created at a time when the peatlands had already subsided considerably as a result of drainage, but large-scale embankment building had not yet taken place.